Шпион его величества: апрель - июль 1812 г., Вильна - Курганов Ефим (Икс-Хистори, 2011)
Экземпляры: ООВ (20140206) / Инвентарный номер: 36312 / Цена: 260.03 / Сис.шифр: 84(2Рос) / Авт.знак: К 93 / ГРНТИ: 17 / ББК: 84(2Рос)